PENGARUH KOMPENSASI DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN - Rahmadi Rahmadi; Iin Susanti Lubis; Yuni Susanti; Dedi Kuswandi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
This study aims to determine the effect of compensation and motivation indirectly on employee performance through job satisfaction at the Tanjungbalai City Education Office. Collecting data in this study using quantitative methods. The sample in this study were all employees at the Tanjungbalai City Education Office, totaling 48 people. The data analysis technique in this research is Intervening. The results of this study indicate that partially compensation has a positive but insignificant effect on employee performance, either indirectly through job satisfaction.